Penambatan molekul senyawa turunan orizanol terhadap enzim 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reduktase - Syaikhul Aziz; Nur Adliani; Sukrasno Sukrasno (Journal of Science and Applicative Technology, 2020)
Oryzanol has been reported to reduce serum total cholesterol (hypolipidemic agent) by inhibiting HMG-CoA reductase, an enzyme responsible for the metabolic pathway that produces cholesterol and isoprenoid. The purpose of this experiment is to determine the inhibition activity of oryzanol derivatives on HMG-CoA reductase by molecular docking. Four structure of oryzanol derivatives, Lanosteryl-ferulate, Brassicasteryl-ferulate, Lupeol-ferulate, and Cholesteryl-ferulate were used as ligands for molecular docking. The HMG-CoA reductase structure was obtained from protein data bank and the study was performed using AutoDock Tools as a molecular docking software. All oryzanol derivatives show binding affinity against HMG-CoA reductase. Lupeol-ferulate was predicted to be the best inhibitory activity against HMG-CoA reductase because of molecular docking.